Research of the Additional Losses Occurring in Optical Fiber at its Multiple Bends in the Range Waves 1310nm, 1550nm and 1625nm Long; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Yurchenko A. V. Aleksey Vasilievich; Gorlov N. I.; Alkina A. D.; Mekhtiyev (Mekhtiev) A. Ali; Kovtun A. A. (2016, 2016)
Title screen